Effect of frying oil quality and TBHQ on the shelf‐life of potato crisps - Asap, Telingai; Augustin, Mary Ann (John Wiley & Sons, 1986)
Three different systems were used for the evaluation of the effect of frying oil quality and tertiarybutyl hydroquinone (TBHQ) on the shelf‐life of fried potato crisps. Batches of potato slices were fried for 4 min at 30 min intervals over a period of 5 h day−1 for eight consecutive days in refined, bleached and deodorised palm olein (RBD olein) without antioxidant (system 1); RBD containing 200 μg g−1 TBHQ at the start of the experiment (system 2) and RBD olein which had TBHQ topped up to a level of 200 μg g−1 at the start of each frying day (system 3). Sensory evaluation of crisps showed that there is an initial rapid decrease in shelf‐life with increase in fry number in all systems. There was only a comparatively smaller effect on shelf‐life with increase in fry number in later fryings. When the shelf‐life of crisps was related to the quality of oil in the frying medium, it was found that the shelf‐life of the product is only slightly affected when the oil had deteriorated beyond the acceptable limit of quality of frying oil, where the acceptable limit was taken as 27‐30% polar components and 1–2 mg potassium hydroxide g−1 oil. TBHQ does have a protective carry‐through effect. The protective effect is more pronounced when TBHQ is topped up to a level of 200 μg g−1 at the beginning of each frying day.